The Search Term ‘Suicide’ Is Being Used to Lead Web Browsers to Online Casinos - Phillips, James G; Chow, Yang-Wai; Rogers, Heather; Blaszczynski, Alex (Informa UK Limited, 2024)
While Search Engine Optimisation seeks to enhance PageRankings, some methods are not approved or condoned by browser developers. To understand the risks faced by suicidal gamblers in the online environment, 2 studies examined the behaviour of an online search engine. A series of Google searches in 2021 used key terms such as ‘suicide’ and ‘gambling’ that might be employed by a suicidal gambler. During these searches browser ‘hits’ included opportunities to gamble. Webpages (N = 200) offered to a potentially suicidal gambler were primarily categorised as: other suicides (20%), treatment providers (8.5%), online casinos (7%); politics (22%), academic (23.5%). From a Google search providing 1,090 hits, the links to 113 online casinos were classified as a function of Domain Name hijacking, Metatag Stuffing, Error 404, and presence of Malware. There were significant relationships between the size of the businesses whose Domain Names were hijacked, and the presence of Malware. The deliberate use by webpage designers of the word ‘suicide’ to attract customers to online casinos appears inappropriate and ethically questionable.
Keywords: 46 Information and Computing Sciences; 3503 Business Systems In Context; 35 Commerce, Management, Tourism and Services; Mental Health; Behavioral and Social Science; Prevention; Suicide Prevention; Suicide; 08 Information and Computing Sciences; 17 Psychology and Cognitive Sciences; Human Factors; 3503 Business systems in context; 4608 Human-centred computing; 5204 Cognitive and computational psychology